Effect of etodolac on methotrexate pharmacokinetics in patients with rheumatoid arthritis (1991)
OBJECTIVE: To determine if the pharmacokinetics of methotrexate (MTX) is modified by the coadministration of etodolac. METHODS: MTX (10 mg) was administered intramuscularly in the absence and presence of steady state levels of etodolac in 19 patients with rheumatoid arthritis. MTX levels were assayed by fluorescence polarization immunoassay. Concentrations of 7-hydroxymethotrexate (7-OH-MTX) were assayed by a reverse phase high performance liquid chromatography method. The unbound fraction was determined by ultrafiltration. RESULTS: When etodolac was coadministered with MTX, the highest observed concentration decreased and the mean residence time increased to become statistically significant. However, these differences are not of great clinical importance especially given that the area under the curve and clearances were unchanged. There were no significant differences in binding protein and 7-OH-MTX concentrations between MTX with and without etodolac administration. CONCLUSION: The pharmacokinetics of MTX is slightly modified by coadministration of etodolac. Moreover, no clinical toxicity was observed.